KONTRIBUSI KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA-TANGAN DENGAN HASIL FREE THROW PADA TIM BASKET PUTRI SMA NEGERI 9 PEKANBARU - Cindi Tania Napitupulu; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this study is based on observations on the women's basketball team at SMA NEGERI 9 Pekanbaru which tends to be seen when athletes make inaccurate free throws, this study aims to determine the contribution of wrist flexion and eye coordination that contribute when free throwing. In this study using the wrist flexion test instrument and hand eye coordination using the catch ball throwing instrument, as well as free throw data using a free throw shooting instrument. The sampling technique was a total sampling of 12 people. From the calculation results of the analysis of the contribution of X and Y that have gone through the process of data processing it can be concluded as follows Rx1y (there is a contribution of wrist flexion with the ability of free throw) = r count 0.61 and the contribution is 37.21%. Rx2y (no contribution of eye-hand coordination with freethrow ability) = rcount of 0.08 and contribution of 0.64%. Rx1x2y (there is a contribution of wrist flexion and eye-hand coordination with the ability of free throw) = rcount of 0.64 and contribution of 40.96%Key Words: Wrist Flexion, Hand Eye Coordination, Free Throw.